(untitled) (Revista Contexto & Saúde, 2025)
Objective: This study aims at exploring caregivers’ perspectives on the bond established in the care of institutionalized children and adolescents. Methods: A qualitative study was conducted with ten caregivers from a child and adolescent care institution in southern Brazil. The participants were selected based on two inclusion criteria: direct involvement in child and adolescent care and minimum tenure of three months at the institution. Data collection took place between October and November 2020 through semi-structured interviews. The data underwent directed content analysis guided by Watson’s Human Care Theory, which served as grounds for developing the initial coding framework. Results: Two categories were obtained: The bond as a form of transpersonal care, which allowed understanding the transpersonal relationships proposed by Jean Watson as a form of care established through the bond between the caregiver and the person cared for; and Care work in bond formation and disruption, which provided insights into how attachment influences the establishment and dissolution of caregiver-child relationships. Conclusion: It is essential to foster bonds and attachment in transpersonal relationships, particularly in the care of children and adolescents, where the caregiver’s role is indispensable. Within institutional care settings, providing emotional support and recognition is crucial for enabling caregivers to establish attachment-based relationships, which are fundamental to children’s and adolescents’ development, especially in the deinstitutionalization context.